Access to formal credit and enterprise performance in Nigeria: a gender perspective - Nwosu, Emmanuel O.; Orji, Anthony (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The main focus of this study is to ascertain the impact of access to formal credit on enterprise performance. The study uses Nigerian Enterprise Surveys data for 2010 to construct a direct measure of credit constraint. From propensity score estimations, the results show that access to formal credit matters and has a significant impact on enterprise performance indicators. Firms that are credit constrained have significantly lower output per worker, capital per worker, employment of labour and investment in fixed assets for expansion compared to firms that are not credit constrained. This is more pronounced for women-owned enterprises after adjusting for bias in the estimations and controlling for sampling weights. This suggests that one way to support the growth of enterprises in Nigeria is to make access to formal credit less stringent. Also, government and monetary authorities should support credit expansion policies for medium and small enterprises in Nigeria
Argument Oeconomica, 2016, Nr 1 (36), s. 191-224
Keywords: entrepreneurs; gender; credit; constraint; access; performance; Propensity Score Matching